The use of fine waste material for the future of sustainable construction - Kalinowska-Wichrowska, Katarzyna (Technical Sciences, 2018)
The article presents data regarding scale of current production of cement and its future of sustainable construction. In the time of sustainability and Union Directives which rightly impose the reduction of emission of greenhouse gases the solution has been proposed that may in some extent contribute to reducing the cement consumption by using properly prepared recycling binder as its substitute. Some results of own research have been presented, connected with the possibility of using the waste material in form of properly processed cement grout as a partial substitute of cement in the cement composites. Due to high content of contaminants in the industrial secondary binder, which might interfere with the uniformity of results, it has been decided to obtain the recycling binder in the laboratory conditions. The secondary mineral material has been obtained in the process of multi-stage disintegration of prepared laboratory samples, made from cement grouts. The prepared material has been analysed for content of dust fraction and pozzolana activity. The obtained results have revealed that in assumed conditions of recycling binder processing it may be successfully used as cement substitute in the cement composites.